Direct copolymerization of ethylene with protic comonomers enabled by multinuclear Ni catalysts - Gang Ji (Nature Portfolio, 2021)
The applications of polyolefins are limited by the nonpolar nature of the polymer. Here the authors show a method to copolymerize ethylene with the protic vinyl acetic acid via well defined multinuclear nickel catalysts.